2015
DOI: 10.1007/s10916-015-0271-x
|View full text |Cite
|
Sign up to set email alerts
|

Spleen Segmentation and Assessment in CT Images for Traumatic Abdominal Injuries

Abstract: Spleen segmentation is especially challenging as the majority of solid organs in the abdomen region have similar gray level range. Physician analysis of computed tomography (CT) images to assess abdominal trauma could be very time consuming and hence, automating this process can reduce time to treatment. The proposed method presented in this paper is a fully automated and knowledge based technique that employs anatomical information to accurately segment the spleen in CT images. The spleen detection procedure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…For instance, the extraction of incidental findings such as pulmonary and thyroid nodules (20)(21)(22) has been demonstrated to be possible with machine learning techniques. Further machine learning research has also been performed for detection of critical findings such as pneumothorax ( Fig 6), fractures, organ laceration, and stroke (23)(24)(25)(26)(27)(28)(29).…”
Section: Automated Detection Of Findingsmentioning
confidence: 99%
“…For instance, the extraction of incidental findings such as pulmonary and thyroid nodules (20)(21)(22) has been demonstrated to be possible with machine learning techniques. Further machine learning research has also been performed for detection of critical findings such as pneumothorax ( Fig 6), fractures, organ laceration, and stroke (23)(24)(25)(26)(27)(28)(29).…”
Section: Automated Detection Of Findingsmentioning
confidence: 99%
“…However, nearly all approaches are designed and tested for CT images, which makes a reliable result comparison with our framework hardly possible. Hence, we cannot compare our results with the work of Belgherbi and Bessaid (2012) and Soroushmehr et al (2015) that are designed for CT image data. Furthermore, the semi-automatic approaches of Belgherbi and Bessaid (2012) and Soroushmehr et al (2015) require user interaction and cannot be compared to our fully automatized framework concept.…”
Section: Discussionmentioning
confidence: 93%
“…A graph cut technique is then applied to segment spleen tissue in reconstructed images. In Soroushmehr et al (2015) the authors propose a slicewise thresholding method beginning with thresholded spleen regions in a region of interest (ROI) of the starting slice. Thresholded regions in the following slices that maximally superpose with the spleen regions of the previous slices are selected as new spleen regions.…”
Section: Related Workmentioning
confidence: 99%
“…Additional ML studies that were carried out identified important findings such as pneumothoraces, fractures, organ lacerations, and stroke. 25 31 …”
Section: Resultsmentioning
confidence: 99%
“…Additional ML studies that were carried out identified important findings such as pneumothoraces, fractures, organ lacerations, and stroke. [25][26][27][28][29][30][31] Interpretation of scans is a frequent discussion area and the topic of contention as to whether such techniques could/would eventually fully replace radiologists. The interpretation of detected findings 'requires a high level of expert knowledge, experience, clinical judgment and correlation based on each clinical scenario'.…”
Section: The Era Of Modern Medicinementioning
confidence: 99%